Human resource shortage in India's health sector: a scoping review of the current landscape - Vini Mehta; Puneeta Ajmera; Sheetal Kalra; Mohammad Miraj; Ruchika Gallani; Riyaz Ahamed Shaik; Hashem Abu Serhan; Ranjit Sah (BMC, 2024)
Abstract Background For healthcare delivery to be optimally effective, health systems must possess adequate levels and we must ensure a fair distribution of human resources aimed at healthcare facilities. We conducted a scoping review to map the current state of human resources for health (HRH) in India and the reasons behind its shortage. Methods A systematic search was conducted in various electronic databases, from the earliest available date till February 2024. We applied a uniform analytical framework to all the primary research reports and adopted the "descriptive-analytical" method from the narrative paradigm. Inductive thematic analysis was conducted to arrange the retrieved data into categories based on related themes after creating a chart of HRH problems. Results A total of 9675 articles were retrieved for this review. 88 full texts were included for the final data analysis. The shortage was addressed in 30.6% studies (n = 27) whereas 69.3% of studies (n = 61) addressed reasons for the shortage. The thematic analysis of data regarding reasons for the shortage yielded five kinds of HRH-related problems such as inadequate HRH production, job dissatisfaction, brain drain, regulatory issues, and lack of training, monitoring, and evaluation that were causing a scarcity of HRH in India. Conclusion There has been a persistent shortage and inequitable distribution of human resources in India with the rural expert cadres experiencing the most severe shortage. The health department needs to establish a productive recruitment system if long-term solutions are to be achieved. It is important to address the slow and sporadic nature of the recruitment system and the issue of job insecurity among medical officers, which in turn affects their other employment benefits, such as salary, pension, and recognition for the years of service.